Geographical Disparities in Blood Pressure and Dietary Patterns: A Comparative Study of Mountainous and Coastal Communities in Gorontalo, Indonesia - Sandalayuk, Marselia; Paramata, Yeni; Pakaya, Ririn; Yasin, Maesarah; Hatta, Herman; Nuryani, Nuryani (Al-Sihah : The Public Health Science Journal, 2024)
Hypertension, a leading cause of early death worldwide, affects 1.94% of the population in Gorontalo Regency, according to the local Health Department. However, limited studies have examined the relationship between hypertension prevalence and dietary patterns among mountain and coastal communities in this region. The purpose of this study was to explore differences in blood pressure and consumption patterns between people living in mountain areas and coastal areas in Gorontalo District. This research employed an analytic observational design with a cross-sectional approach. The study included 126 participants living in mountain and coastal areas of Gorontalo District, selected using a cluster random sampling technique. Data were collected using a 24-hour food recall questionnaire and a tension meter. The data were analyzed using the chi-square test. The findings revealed no significant differences in systolic blood pressure (p = 0.359, p > 0.05), diastolic blood pressure (p = 0.160, p > 0.05), or sodium consumption patterns (p = 0.324, p > 0.05) between residents of mountainous and coastal areas. However, significant differences were found in fat consumption patterns (p = 0.000, p < 0.05) and carbohydrate consumption patterns (p = 0.004, p < 0.05) between the two groups. It is recommended that residents regularly monitor their blood pressure to detect potential increases and reduce excessive salt consumption.